Multi-Omics Unveils Inflammatory Regulation of Fermented Sini Decoction Dregs in Broilers Infected with Avian Pathogenic Escherichia coli - Shuanghao Mo; Xin Fang; Wenxi Xiao; Bowen Huang; Chunsheng Li; Hui Yang; Yilin Wu; Yiming Wang; Hongxia Ma (Veterinary Sciences)
Avian colibacillosis causes significant economic losses and raises concerns for human health due to food safety risks, a problem exacerbated by the increase in antibiotic resistance. This study aimed to develop novel antibacterial strategies using fermented liquid of Sini decoction dregs to address these challenges. We analyzed the transcriptome of the chicken thymus sample GSE69014 in the GEO database to identify immune-related genes, performed molecular docking to assess compound interactions, and experimental validation via Western blot and ELISA to evaluate anti-inflammatory effects. Results revealed 11 core genes, including TLR4, critical for immune responses against the infection, with TLR4 activating key inflammatory pathways. Fermented liquid with probiotics enhanced bioactivity, and natural compounds Dioscin and Celastrol from the fermented liquid inhibited inflammation by targeting the TLR4-MD2 complex. In animal models, fermented liquid outperformed individual compounds, likely due to synergistic effects, significantly reducing inflammatory markers. These findings demonstrate that fermented liquid of Sini decoction dregs offers a promising, sustainable approach to control avian colibacillosis, mitigate antibiotic resistance, and improve poultry health, providing a scientific foundation for its application in farming to reduce economic losses and enhance food safety.